Resveratrol Alleviating the Ovarian Function Under Oxidative Stress by Alternating Microbiota Related Tryptophan-Kynurenine Pathway - Wang, Jianping; Jia, Ru; Celi, Pietro; Zhuo, Yong; Ding, Xuemei; Zeng, Qiufeng; Bai, Shiping; Xu, Shengyu; Yin, Huadong; Lv, Li; Zhang, Keying (Frontiers in Immunology, 2022)
Oxidative stress is a key factor regulating the systemic pathophysiological effects and a fundamental reason associated with reduction in fertility in old laying hens. Previous studies revealed that resveratrol (RV) exhibits a preventive effect against oxidative stress in the ovary. However, it remains unknown whether gut microbiota respond to resveratrol during an OS challenge. In Exp. 1, layers received either resveratrol (0 or 600 mg/kg) or intraperitoneal injection of tert-butyl hydroperoxide (tBHP) (0 or 800 μmol/kg BW) for 28 days. In Exp. 2, the role of intestinal microbiota on the effects of resveratrol on tBHP-induced oxidative stress was assessed through fecal microbiota transplantation (FMT). The OS challenge decreased the reproduction performance and ovarian function as mainly demonstrated by reduction of laying rate and lower pre-hierarchical follicles and higher atretic follicles. Oral RV supplementation ameliorated egg laying rate reduction and gut microbiota dysbiosis. RV also reversed the tryptophan-kynurenine pathway, up-regulated the expression of silent information regulator 1(SIRT1), the nuclear factor E2-related factor 2 (Nrf2) and decreased the P53, and FoxO1 expression. These findings indicated that intestinal microbiota related tryptophan-kynurenine pathway is involved in the resveratrol-induced amelioration of ovary oxidative stress induced by tBHP in layer model, while SIRT1-P53/FoxO1 and Nrf2-ARE signaling pathway were involved in this process.